2018
DOI: 10.1080/15569543.2018.1438472
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of ochratoxin A in Algerian wheat and its milling derivatives

Abstract: To determine the concentrations of ochratoxin A in wheat, and its derivatives, 81 samples, including durum wheat (n ¼ 27), common wheat (n ¼ 12), semolina (n ¼ 29) and flour (n ¼ 13) were collected from regions of Algeria. The results showed that 62 of the 81 samples (76.54%), were contaminated with quantities of ochratoxin A ranging from 0.84 to 34.75 mg/kg. The results showed that 69.23% of wheat grains were contaminated with ochratoxin A (0.21-27.31 mg/kg). Ochratoxin A were detected both in semolina and fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…These results for OTA concentration were considered below the maximum limit (5 μg/kg) set by the Egyptian Organization for Standardization and Quality Control [ 32 ] and European Commission [ 39 ] for wheat grains. Several studies reported the occurrence of OTA in wheat in North African countries [ [40] , [41] , [42] , [43] , [44] , [45] ]. Joubrane et al [ 34 ] recorded that 28.21 % of wheat samples collected during the 2008 cultivation season from Lebanon were contaminated with OTA at concentrations (>3 μg/kg), while 19.20 % of wheat samples collected during the 2009 cultivation season were contaminated with OTA at concentrations (>3 μg/kg).…”
Section: Resultsmentioning
confidence: 99%
“…These results for OTA concentration were considered below the maximum limit (5 μg/kg) set by the Egyptian Organization for Standardization and Quality Control [ 32 ] and European Commission [ 39 ] for wheat grains. Several studies reported the occurrence of OTA in wheat in North African countries [ [40] , [41] , [42] , [43] , [44] , [45] ]. Joubrane et al [ 34 ] recorded that 28.21 % of wheat samples collected during the 2008 cultivation season from Lebanon were contaminated with OTA at concentrations (>3 μg/kg), while 19.20 % of wheat samples collected during the 2009 cultivation season were contaminated with OTA at concentrations (>3 μg/kg).…”
Section: Resultsmentioning
confidence: 99%
“…They may also be human carcinogens (Group 2B) [ 213 , 214 ], and are known to be teratogenic, mutagenic, hepatotoxic and immunosuppressive [ 212 , 214 ]. In some areas, e.g., Algeria, nearly 70% of the wheat samples tested contained OTA [ 215 ]. Biosynthesis of OTA usually occurs in storage, so resistance to ochratoxin accumulation is not a common breeding target in wheat.…”
Section: Toxinsmentioning
confidence: 99%
“…From a survey in Canada, five wheat samples (2.2%) were detected with OTA and OTB, and only three samples exceeded 5 µg/kg [35]. For Algeria, the situation was worse, with 62 of 81 wheat samples contaminated with OTA ranging from 0.84 to 34.75 µg/kg [36]. Researchers also found the flour manufacturing process had little impact on OTA elimination.…”
Section: Ota In Cerealsmentioning
confidence: 99%